A Novel Content Based Image Retrieval for Human Brain Tumor Magnetic Resonance Imaging - Sujiya , S.; Jeevaprabha , K.; Jegatheeswari , I. (International Journal of Membrane Science and Technology, 2023)
With increasing amount in neuro patients which increases workload on small group of radiologists, a new system is needed that help radiologists for getting essential information like types of image, extraction of tumor and retrieve the similar images for references to take treatment planning for neuro patient. CBIR is the method by that one searches for similar pictures in keeping with the content of the similar image, like color, texture, shape, then forth. The field of representing, organizing and searching images based on their content rather than image annotations. A method framework with efficiency retrieving images from a group by similarity. The retrieval depends on extracting the acceptable characteristic quantities describing the specified contents of images. Additionally, appropriate querying, matching, categorization are needed. This approach retrieves or searches digital images from giant databases exploitation the content of the image themselves or syntactic image options without human involvement. To assist image retrieval, techniques from statistics, pattern recognition, signal process, and computerized vision are deployed commonly. Different terms used interchangeably for CBIR by image content (QBIC) and content-based visual info retrieval (CBVIR).